Hijack or release? On the heuristic limits of the frame of instrumentalization of religion for discussing the entanglements of populism, religion, and gender. Issue 4 (4th July 2022) - Giorgi, Alberta
ABSTRACT: In the Manichaean discourse of the radical-right populist parties, both religion and gender play a role in the discursive process of 'othering'. At the same time, on some occasions, populist discourse also mobilises Christianity and gender equality against immigrants, which has been interpreted through the frames of hijacking or instrumentalization. In this paper, I advance two arguments: first, I illustrate the relevance of the literature on secularisation to finetune the analysis of the entanglements of populism, religion and gender, to overcome the 'hijacking' frame; second, I make a plea for a socio-constructivist perspective, which pays attention to how the actors make sense of their religious-political engagement and try to avoid paternalistic interpretations. Empirical analysis focuses on the discourse of the supporters of Matteo Salvini, the leader of the Italian radical-right populist party Lega Nord, on Instagram, showing the intersections of religion and gender.